2002
DOI: 10.1079/bjn2002565
|View full text |Cite
|
Sign up to set email alerts
|

Total body phylloquinone and its turnover in human subjects at two levels of vitamin K intake

Abstract: The aims of this study were to determine the total body phylloquinone and its metabolic turnover in human subjects using a tracer dose of [5-H 3 ]phylloquinone containing 55·5 £ 10 4 MBq=mmol. Seven subjects aged 22 to 49 years were given 0·3 mg isotopic phylloquinone intravenously on a control diet (75 mg phylloquinone/d) and blood, urine and faeces were sampled periodically for 6 d. Five of these subjects were studied a second time after 3 -8 weeks on a low-vitamin K diet (8 mg/d). The changes in the radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 37 publications
7
33
1
Order By: Relevance
“…The average values of the corresponding parameters found in the present experiments most closely resemble the values obtained by Shearer et al (1972Shearer et al ( , 1974, Shepherd et al (1977) and Bjornsson et al (1979) rather than those more recently reported by Olson et al (2002) (see Table 3). …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The average values of the corresponding parameters found in the present experiments most closely resemble the values obtained by Shearer et al (1972Shearer et al ( , 1974, Shepherd et al (1977) and Bjornsson et al (1979) rather than those more recently reported by Olson et al (2002) (see Table 3). …”
Section: Discussionsupporting
confidence: 92%
“…Thus, if irreversible disposal occurred at a greater rate than that predicted, absorption would be under-estimated. However, our data are similar to those previously published with the exception of the Olson et al (2002) which suggested slower rates of disposal, and that would lead, in our model, to lower estimates of absorption.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations